The relationship of spiritual intelligence and social support with academic resilience emigrant college students in Surabaya - Silalahi, Silvia Gazella; Sukiatni, Dwi Sarwindah; Kusumandari, Rahma (Fakultas Psikologi Universitas 17 Agustus 1945 Surabaya, 2024)
Academic resilience is an individual's ability to recover from difficulties and pressure in academics. This research aims to determine the relationship between spiritual intelligence and social support and academic resilience. This research uses a quantitative method with an accidental sampling technique, which is a method of determining samples based on chance, meaning that anyone who happens to meet the researcher can be used as a sample, if the person accidentally met is deemed suitable as a data source. The measuring instruments used include the academic resilience scale with 32 items, the spiritual intelligence scale with 34 items, and the social support scale with 38 items. The sample for this research consisted of 100 migrant students in Surabaya. These results indicate a significant positive relationship between spiritual intelligence, social support, and academic resilience among emigrant college students in Surabaya.